2012
DOI: 10.5539/ijps.v4n4p69
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Gender Equivalence and Bias in a Measure of Psychological Hardiness

Abstract: One of the most pervasive criticisms found in the hardiness literature concern the question whether the construct is equally important for men and women. Using a multi-group confirmatory factor analytic approach, this question was explored from a more fundamental perspective by examining measurement equivalence across gender in a measure of hardiness, the 15-item Dispositional Resilience Scale Bartone, P. T. (1995). A short hardiness scale. Paper presented at the Annual Convention of the American Psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Black women reveal higher levels of hardy challenge than their white counterparts (Ferreira, 2012). Research also suggests that even though men tend to score higher on overall hardiness, women tend to score higher on hardy control (Hystad, 2012).…”
Section: The Relationship Between Gender Hardiness and Career Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Black women reveal higher levels of hardy challenge than their white counterparts (Ferreira, 2012). Research also suggests that even though men tend to score higher on overall hardiness, women tend to score higher on hardy control (Hystad, 2012).…”
Section: The Relationship Between Gender Hardiness and Career Adaptabilitymentioning
confidence: 99%
“…Black women reveal higher levels of hardy challenge than their white counterparts (Ferreira, 2012). Research also suggests that even though men tend to score higher on overall hardiness, women tend to score higher on hardy control (Hystad, 2012). The construct of career adaptability has its origins in career construction theory which is closely associated with the vocational psychology model of vocational development (Hartung, 2011;Maree, 2013;Savickas, 1997Savickas, , 2005Savickas, , 2013.…”
mentioning
confidence: 99%
“…That psychological hardiness is equally important for the two sexes is further supported by studies that have included both sexes and found that men and women generally do not differ in their mean hardiness scores (e.g., Klag & Bradley, 2004;Manning, Williams & Wolfe, 1998;Roth, Wiebe, Fillingim & Shay, 1989;Skirka, 2000;Soderstrom et al, 2000;Taft, Stern, King & King, 1999). Furthermore, in a more fundamental study of the hardiness concept, Hystad (2012) explored whether the DRS-15 (Bartone, 1995) used to measure hardiness actually measured the same construct in male and female subjects. The results showed nonequality in only two of the items belonging to the control subscale, and these differences could be characterized as small at best.…”
Section: Discussionmentioning
confidence: 91%
“…The DRS-15 uses both positively and negatively keyed items, and includes three factors of resilience: commitment, control and challenge (Bartone, 2006), each measured by five items scored on a four-point scale ranging from “not at all true” to “completely true.” Example items comprise: “Most of my life gets spent doing things that are meaningful” (commitment), “By working hard, you can nearly always achieve your goals” (control), and “Changes in routine are interesting to me” (challenge) (Bartone et al, 2012; Kelly et al, 2014). When the six negatively keyed items are reversed, a total score for resilience can be calculated by adding scores for all items (Hystad, 2012). For the present study, as numerous respondents were missing scores for particular items of the DRS-15, a total score for each respondent was calculated by averaging rather than adding scores.…”
Section: Methodsmentioning
confidence: 99%